Study of the Effect of Carbopol and Chitosan on the Gelatin Water Solvation Process with the Method of Molecular Dynamics - Mayorova AV (Journal of Global Pharma Technology, 2017)
Background: The purpose of the paper is the analysis of scientific and technical information concerning features of using microcapsules in dermal medicinal and cosmetic products, as well as a theoretical study of the effect of carbopol and chitosan on the process of gelatin solvation in microcapsules. An analysis of published data showed urgency of developing dermal medicinal and cosmetic forms using microencapsulation, as well as the prospects for studying the relationship between the material of microcapsules and chemical composition of the drug. Carbopol 940 and chitosan succinate were used as the basic carrier for the developed dosage forms. A statistically significant increase in the solvation level of gelatin in the presence of carbopol at the human body temperature compared to solvation with pure water was established by the molecular dynamics method with the use of the Bio Evrica software. In a similar way, an insignificant effect of the ionized form of chitosan on the level of gelatin solvation was found. Methods: The molecular dynamics simulation was performed with direct account of the solvent molecules, the charges of carbopol and chitosan atoms were calculated previously by abinitio method (6-311G**).Conclusion:  The obtained results show the expediency of using carbopol and chitosan as the basic carrier of external dosage forms with gelatinous microcapsules, since increasing the gelatin solvation level promotes the release of active substance of microcapsules.Keywords: Molecular dynamics, Solvation, Gelatin, Carbopol 940, Chitosan microcapsules, Gel.